2017
DOI: 10.3390/ijerph14060596
|View full text |Cite
|
Sign up to set email alerts
|

Associations among Screen Time and Unhealthy Behaviors, Academic Performance, and Well-Being in Chinese Adolescents

Abstract: Screen time is negatively associated with markers of health in western youth, but very little is known about these relationships in Chinese youth. Middle-school and high-school students (n = 2625) in Wuhan, China, completed questionnaires assessing demographics, health behaviors, and self-perceptions in spring/summer 2016. Linear and logistic regression analyses were conducted to determine whether, after adjustment for covariates, screen time was associated with body mass index (BMI), eating behaviors, average… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 42 publications
6
75
0
5
Order By: Relevance
“…We observed that increased screen time (>2 hours per day) increased odds of breakfast skipping by almost 18%, in both sexes. Data from Chinese adolescents suggested a link between electronic games and skipping breakfast, both on school days and non‐school days . Also, a study among 12 642 US students showed that television viewing was positively related to skipping breakfast after adjustment for several confounders .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that increased screen time (>2 hours per day) increased odds of breakfast skipping by almost 18%, in both sexes. Data from Chinese adolescents suggested a link between electronic games and skipping breakfast, both on school days and non‐school days . Also, a study among 12 642 US students showed that television viewing was positively related to skipping breakfast after adjustment for several confounders .…”
Section: Discussionmentioning
confidence: 99%
“…Data from Chinese adolescents suggested a link between electronic games and skipping breakfast, both on school days and non-school days. 31 Also, a study among 12 642 US students showed that television viewing was positively related to skipping breakfast after adjustment for several confounders. 16 Similarly, a systematic review including children 1-18 years revealed a positive association between TV viewing and unhealthy dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…The most studied aspect was depression, with 23 (29%) studies examining the relationship between social media use and depressive symptoms (Ferguson et al, 2014;Neira and Barber, 2014;O'Connor et al, 2014;Banjanin et al, 2015;Richards et al, 2015;Spears et al, 2015;Tseng and Yang, 2015;Fahy et al, 2016;Banyai et al, 2017;Brunborg et al, 2017;Colder Carras et al, 2017;Larm et al, 2017;Nesi et al, 2017a;Salmela-Aro et al, 2017;Fredrick and Demaray, 2018;Houghton et al, 2018;Niu et al, 2018;Twenge et al, 2018;Wang et al, 2018;Wartberg et al, 2018). Twenty of the included studies focused on different aspects of good mental health, such as well-being, happiness, or quality of life (Best et al, 2014(Best et al, , 2015Bourgeois et al, 2014;Ferguson et al, 2014;Cross et al, 2015;Koo et al, 2015;Richards et al, 2015;Spears et al, 2015;Fahy et al, 2016;Foerster and Roosli, 2017;Przybylski and Bowes, 2017;Yan et al, 2017;Booker et al, 2018;de Lenne et al, 2018;Erfani and Abedin, 2018;Erreygers et al, 2018;Lai et al, 2018;…”
Section: Mental Health Foci Of Included Studiesmentioning
confidence: 99%
“…A study with the largest representative sample of school-aged children and adolescents in China found that the prevalence of obesity increased from 0.2% to 8.1% between 1985 and 2010 ( Song et al, 2013 ). Many factors are associated with physical activity in Chinese youth, including psychological, social, environmental, and systemic ( Tudor-Locke et al, 2003 ; Abdullah et al, 2005 ; Yan et al, 2017 ; Zhang et al, 2016 ). For example, Shi and colleagues ( Shi et al, 2006 ) reported that Chinese girls with low socioeconomic status (SES) had the highest levels of physical activity, while boys with high SES reported the lowest rates of walking to school.…”
Section: Introductionmentioning
confidence: 99%